THE EXTENT AND DETERMINANTS OF DISCLOSURE OF GLOBAL REPORTING INITIATIVE GUIDELINES: AUSTRALIAN EVIDENCE - Christopher, Theo; Filipovic, Mirela (The journal of contemporary issues in business and government, 2008)
This research paper examines the extent and determinants of disclosure of the Global Reporting Initiative (GRI) in a sample of Australian listed companies. The extent of disclosure was found to be extremely low and selective, differ across industries and couched in general terms. Positive Accounting Theory was used to formulate hypotheses to GRI disclosure in the 2004 annual report of 450 companies listed on the Australian Stock Exchange. It was hypothesised that GRI disclosure would be positively related to ownership, leverage, big four audit firms (BFAFs), size of the firm, profitability and industry type. A multivariate regression analysis was completed and the results supported a significant positive relation with ownership, leverage, size of the firm and industry type. The remaining two variables, BFAFs and profitability, were not found to be significantly related to GRI disclosure but supported a positive relationship.